0 × 0\times\infty and 1 1^\infty

Calculus Level 4

A = lim n ( 1 + 1 n ) n B = lim n n [ ( 1 + 1 n ) n A ] \begin{aligned} A & = \lim_{n\to \infty} \left(1+\frac{1}{n}\right)^n \\ B & =\lim_{n\to \infty} n\left[\left(1+\frac{1}{n}\right)^n-A\right] \end{aligned}

Find B A \dfrac{B}{A} .


The answer is -0.5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Chew-Seong Cheong
Nov 13, 2019

First consider

A = lim n ( 1 + 1 n ) n = lim n ( 1 + n n + n ( n 1 ) 2 ! n 2 + n ( n 1 ) ( n 2 ) 3 ! n 3 + + 1 n n ) = lim n ( 1 + 1 + 1 2 ! ( 1 1 n ) + 1 3 ! ( 1 3 n + 2 n 2 ) + + 1 n n ) = 1 0 ! + 1 1 ! + 1 2 ! + 1 3 ! + = e \begin{aligned} A & = \lim_{n \to \infty} \left(1+\frac 1n \right)^n \\ & = \lim_{n \to \infty} \left(1 + \frac nn + \frac {n(n-1)}{2!n^2} + \frac {n(n-1)(n-2)}{3!n^3} + \cdots + \frac 1{n^n} \right) \\ & = \lim_{n \to \infty} \left(1 + 1 + \frac 1{2!}\left(1- \frac 1n\right) + \frac 1{3!}\left(1 - \frac 3n + \frac 2{n^2} \right) + \cdots + \frac 1{n^n} \right) \\ & = \frac 1{0!} + \frac 1{1!} + \frac 1{2!} + \frac 1{3!} + \cdots \\ & = e \end{aligned}

Since A = e A=e , the Euler's number , we have

B = lim n n ( ( 1 + 1 n ) n e ) = lim n n ( 1 + 1 + 1 2 ! ( 1 1 n ) + 1 3 ! ( 1 3 n + 2 n 2 ) + + 1 n n e ) = lim n n ( 1 2 ! n 1 3 ! ( 3 n 2 n 2 ) 1 4 ! ( 6 n 11 n 2 + 6 n 3 ) ) = lim n ( 1 2 ! 1 3 ! ( 3 2 n ) 1 4 ! ( 6 11 n + 6 n 2 ) ) = 1 2 1 2 1 4 1 12 = 1 2 ( 1 0 ! + 1 1 ! + 1 2 ! + 1 3 ! + ) = e 2 \begin{aligned} B & = \lim_{n \to \infty} n \left(\left(1+\frac 1n \right)^n - e \right) \\ & = \lim_{n \to \infty} n \left(1 + 1 + \frac 1{2!}\left(1- \frac 1n\right) + \frac 1{3!}\left(1 - \frac 3n + \frac 2{n^2} \right) + \cdots + \frac 1{n^n} - e \right) \\ & = \lim_{n \to \infty} n \left(-\frac 1{2!n} - \frac 1{3!}\left(\frac 3n - \frac 2{n^2} \right) - \frac 1{4!}\left(\frac 6n - \frac {11}{n^2} + \frac 6{n^3} \right) - \cdots \right) \\ & = \lim_{n \to \infty} \left(-\frac 1{2!} - \frac 1{3!}\left(3 - \frac 2n \right) - \frac 1{4!}\left(6 - \frac {11}n + \frac 6{n^2} \right) - \cdots \right) \\ & = - \frac 12 - \frac 12 - \frac 14 - \frac 1{12} - \cdots \\ & = -\frac 12 \left(\frac 1{0!} + \frac 1{1!} + \frac 1{2!} + \frac 1{3!} + \cdots\right) \\ & = - \frac e2 \end{aligned}

Therefore, B A = e 2 e = 1 2 = 0.5 \dfrac BA = \dfrac {-\frac e2}e = - \dfrac 12 = \boxed{-0.5}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...